[OP.5A.03] NOVEL STRATEGIES TO IMPROVE THE MANAGEMENT OF ALBUMINURIA IN HYPERTENSIVE DIABETIC PATIENTS. (September 2017) - Hamet, P.; Guertin, M.-R.; Dumas, P.; Tahir, R.; Sylvestre, M.-P.; Kaczorowski, J.; Kushnarev, M.; Santucci, L.; Corbeil, G.; Long, C.; Tremblay, J.
Abstract : Objective: After progressing with identification of genomic determinants of diabetic nephropathy, we evaluated the management of microalbuminuria in hypertensive patients with type 2 diabetes (T2D). Design and method: Clinical Practice in Diabetes Study (NCT01907958) is a multicenter stepped wedge cluster randomized trial of family practice clinics comparing the effect of introducing a Point of Care Testing (POCT) for urine albumin to usual practice in hypertensive patients with T2D and genetic testing in general practice. A total of 8 sites were involved, totaling 244 patients with uncontrolled hypertension followed for a period of 18 months. Sites were randomized to implement POCT sequentially. Results: At entry, 40% of patients were found to have albuminuria and 72% to have HbA1c > 6.5%. Albumin/creatinine ratio correlated with systolic blood pressure (SBP) (r = 0.113, p-value = 0.015) and HbA1c (r = 0.22, p-value = 0.001). SBP was not statistically different between microalbuminuric and normoalbuminuric patients (144 mmHg for both, p-value = 0.92) and HbA1c (7.3 for both, p-value = 0.89), suggesting that microalbuminuria cannot be predicted from uncontrolled BP or HbA1c without its direct measurement. Introduction of POCT led to an increase in normoalbuminuric patients over the course of the study (from 55% to 67%) while the percentage of normoalbuminuric patients did not increase in the control group. More patients also reached the target BP of 130/80 mmHg in those exposed to POCT (54%) compared to controls (38%). Among those who had reached the target SBP, 77% were receiving a combination therapy that included an ACEI or an ARB. Gene expression analyses identified 301 differentially expressed genes between patients who progressed from normo- to micro- and from micro- to macro-albuminuria with 132 genes associated to kidney phenotypes. Conclusions: There is a need for improvement in diagnosis and management of albuminuria in hypertensive T2D patients. Implementation of a POCT for albuminuria increased the number of patients at target BP and normal albuminuria. High BP and HbA1c are poor indicators of kidney damage. Genetic markers that correlate with albuminuria in hypertensive patients with T2D should be considered as future biomarkers for treatment initiation.